A Systems Biology Approach to Investigating Sex Differences in Cardiac Hypertrophy. Issue 8 (19th August 2017) - Harrington, Josephine; Fillmore, Natasha; Gao, Shouguo; Yang, Yanqin; Zhang, Xue; Liu, Poching; Stoehr, Andrea; Chen, Ye; Springer, Danielle; Zhu, Jun; Wang, Xujing; Murphy, Elizabeth
Abstract : Background: Heart failure preceded by hypertrophy is a leading cause of death, and sex differences in hypertrophy are well known, although the basis for these sex differences is poorly understood. Methods and Results: This study used a systems biology approach to investigate mechanisms underlying sex differences in cardiac hypertrophy. Male and female mice were treated for 2 and 3 weeks with angiotensin II to induce hypertrophy. Sex differences in cardiac hypertrophy were apparent after 3 weeks of treatment. RNA sequencing was performed on hearts, and sex differences in mRNA expression at baseline and following hypertrophy were observed, as well as within‐sex differences between baseline and hypertrophy. Sex differences in mRNA were substantial at baseline and reduced somewhat with hypertrophy, as the mRNA differences induced by hypertrophy tended to overwhelm the sex differences. We performed an integrative analysis to identify mRNA networks that were differentially regulated in the 2 sexes by hypertrophy and obtained a network centered on PPARα (peroxisome proliferator‐activated receptor α). Mouse experiments further showed that acute inhibition of PPARα blocked sex differences in the development of hypertrophy. Conclusions: The data in this study suggest that PPARα is involved in the sex‐dimorphic regulation of cardiac hypertrophy.